The commercial school heterarchy. Issue 2 (3rd March 2020) - Enright, Eimear; Hogan, Anna; Rossi, Tony
ABSTRACT: This paper explores the rise of philanthropy and the influence corporate partnerships have on the practice of public schooling. We do this by focusing on one public school in Australia and its partnership with one global commercial actor. The paper proceeds by outlining new philanthropy in public schooling and in particular, how commercial organisations are now sponsoring or making donations to local public schools as part of their focus on Corporate Social Responsibility. We then analyse the participation of one commercial actor – McDonald's – in what we are conceptually referring to as the commercial school heterarchy. Our data demonstrates how McDonald's used different kinds of power to market its brand, gain entry into the school and diversify its field of influence from that of 'sponsor' of a sports team to that of a 'business partner'. In our discussion we consider the implications of this partnership for principled positions in public schooling.